2021
DOI: 10.3389/fpsyt.2021.716722
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Analysis Reveals Shared Pathways in Peripheral Blood Mononuclear Cells and Brain Tissues of Patients With Schizophrenia

Abstract: Background: Schizophrenia is a serious mental disorder with complicated biological mechanisms. Few studies explore the transcriptional features that are shared in brain tissue and peripheral blood. In the present study, we aimed to explore the biological pathways with similar expression patterns in both peripheral blood mononuclear cells (PBMCs) and brain tissues.Methods: The present study used transcriptomics technology to detect mRNA expression of PBMCs of 10 drug-naïve patients with schizophrenia and 20 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Interestingly, a down-regulation of the expression of several ATP-synthase-encoding genes and numerous proteasome subunit genes was recently demonstrated in the brain of patients with schizophrenia [55,56]. More importantly, Song et al found that the transcripts associated with mitochondrial oxidative phosphorylation have similar expression patterns in blood immune cells and brain tissues in patients with schizophrenia [57]. It should be mentioned that despite distinct clinical symptoms, the accumulation of misfolded or aggregated proteins in the brain is characteristic of many neurodegenerative disorders, such as amyotrophic lateral sclerosis, Huntington's disease, Parkinson's disease, or Alzheimer's disease.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a down-regulation of the expression of several ATP-synthase-encoding genes and numerous proteasome subunit genes was recently demonstrated in the brain of patients with schizophrenia [55,56]. More importantly, Song et al found that the transcripts associated with mitochondrial oxidative phosphorylation have similar expression patterns in blood immune cells and brain tissues in patients with schizophrenia [57]. It should be mentioned that despite distinct clinical symptoms, the accumulation of misfolded or aggregated proteins in the brain is characteristic of many neurodegenerative disorders, such as amyotrophic lateral sclerosis, Huntington's disease, Parkinson's disease, or Alzheimer's disease.…”
Section: Resultsmentioning
confidence: 99%
“…According to this integrative approach, both biochemical factors (e.g., hormones, neurotransmitters, growth factors, pro- and anti-inflammatory cytokines) and environmental, genetic, and psychosocial factors may contribute and play a role in the pathophysiology of depression. Examining depression patients through immune system cells provides a novel and distinct perspective compared to the traditional serum or plasma approach; moreover, several authors have proposed PBMC as a useful tool for searching biomarkers of neuropsychiatric disorders [ 8 , 67 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analyses with mononuclear cells, plasma, or serum obtained from peripheral blood samples have increasingly impacted clinical research [ 4 7 ]. Notably, peripheral blood mononuclear cells (PBMCs) have great diagnostic power because of the high correlation observed at the transcriptomic level between these cells and the brain [ 8 ]. The identification of potential biomarkers of depression in PBMCs may help to improve the diagnosis of depression, stratify patients and personalize treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RPL30 has also been identified as a potential biomarker or therapeutic target for depression [48] and schizophrenia [49]. A recent study has shown that the hepatocarcinogenesis through NAFLD&NASH was induced through DNA methylation of RPL30 [50].…”
Section: Discussionmentioning
confidence: 99%